Preparation method of PIL-MOF composite membrane and application of PIL-MOF composite membrane in CO2 / N2 separation

The PIL-MOF composite membrane was prepared by PET base membrane pretreatment, UiO-66-NH2 in situ growth and photoinitiated polymerization, which solved the problems of pore blockage and low permeability, achieved efficient CO2/N2 separation and mechanical stability, and improved CO2 adsorption capacity and selectivity.

CN120662134AInactive Publication Date: 2025-09-19NANTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510810011.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing PIL and MOF composite membranes suffer from pore clogging, low permeability and poor mechanical stability in CO2/N2 separation, which limits their performance in practical applications.

Method used

The PIL-MOF composite membrane was prepared by PET base film pretreatment, UiO-66-NH2 in situ growth and photoinitiated polymerization. The UiO-66-NH2 metal organic framework layer grown on the PET substrate and the surface grafted polyionic liquid polymer layer were combined to form a multi-step modified composite membrane.

Benefits of technology

It achieves efficient separation of CO2/N2, improves CO2 adsorption capacity and selectivity, enhances mechanical strength and permeability, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662134A_ABST
    Figure CN120662134A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas separation membrane materials, in particular to a preparation method of a PIL-MOF composite membrane and application of the PIL-MOF composite membrane in CO2 / N2 separation.The preparation method comprises the steps that S1, a PET base membrane is pretreated, specifically, the PET membrane is soaked in a 3M HNO3 solution for 8-12 hours, washed with deionized water to be neutral and then dried; s2, in-situ growth of UiO-66-NH2: dissolving zirconium tetrachloride in acetic acid, preserving heat at 80 DEG C for 0.5-1.5 hours, cooling, adding DMF and 2-aminoterephthalic acid to form a precursor solution, dipping the pretreated PET film for 1-3 hours, and performing solvothermal reaction at 110-130 DEG C for 18-24 hours to obtain a PET / UiO-66-NH2 film; and S3, photo-initiation polymerization: coating the surface of the PET / UiO-66-NH2 film with a solution containing [VBIM] [BF4], a cross-linking agent and a photoinitiator, carrying out 365 nm ultraviolet light curing for 0.5-2 h, and drying to obtain the PIL-MOF composite film. The composite membrane combines the porous characteristic of the metal organic framework and the functional characteristic of the ionic liquid, and has application value in the fields of gas separation, catalysis and the like; the preparation process is simple, the interface bonding strength is high, and the product performance is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas separation membrane materials, and in particular to a method for preparing a PIL-MOF composite membrane and its application in CO2 / N2 separation. Background Art

[0002] Metal-organic frameworks (MOFs) have become paradigm-shifting materials for molecular separations due to their engineered porosity and ultrahigh surface area. Their hierarchical pore structure with tunable pore sizes (3-5 Å) enables precise screening of CO₂ (3.3 Å) from N₂ (kinetic diameter: 3.6 Å). Composites integrating MOFs with polymeric or inorganic supports exhibit improved mechanical stability in industrial-scale operations. While integrating MOF nanocrystals into continuous matrices can improve processability, conventional composite membranes typically suffer from low pore utilization (<40% of theoretical capacity) and inlet blockage when processing gas mixtures such as CO₂ / N₂, limiting their performance in practical applications.

[0003] Ionic liquids (ILs) are a class of organic ionic salts characterized by low volatility and stable structures. They have been widely used in the synthesis of functional materials. ILs are typically composed of positive and negative ions, and novel ILs can be generated through ion exchange reactions, thus enriching their diverse class. Ionic liquids possess large cations, and groups such as unsaturated double bonds can be incorporated into their backbone structures. This enables polymerization, resulting in the formation of polyionic liquids (PILs), which has enriched their types and applications. The positively charged cations in ILs / PILs can undergo Lewis acid-base interactions with electron-rich CO2 molecules, imparting a high CO2 affinity. Despite their excellent CO2 adsorption capacity, ILs have limited CO2 permeability due to their lack of interconnected pore structures. To address this issue, researchers have attempted to immobilize PILs on porous materials; however, challenges such as uneven dispersion and low loading capacity persist, resulting in suboptimal separation performance. While porous materials such as MOFs and COFs offer well-defined pore structures, their separation efficiency is often hampered by pore clogging under mixed gas conditions. These limitations highlight the urgent need for advanced PIL-modified porous membranes with molecular recognition capabilities. Summary of the Invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and propose a method for preparing a PIL-MOF composite membrane and its application in CO2 / N2 separation, which can solve the problems of pore blockage, low permeability and poor mechanical stability in the prior art and achieve efficient CO2 / N2 separation.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a PIL-MOF composite membrane comprises the following steps:

[0007] Step S1, PET base film pretreatment: soak the PET film in 3M HNO3 solution for 8-12 hours, wash with deionized water until neutral and then dry;

[0008] Step S2, in situ growth of UiO-66-NH2: zirconium tetrachloride is dissolved in acetic acid, kept at 80°C for 0.5-1.5 hours, and then cooled. DMF and 2-aminoterephthalic acid are added to form a precursor solution. The pretreated PET film is immersed in the solution for 1-3 hours, and then a solvothermal reaction is carried out at 110-130°C for 18-24 hours to obtain a PET / UiO-66-NH2 film.

[0009] Step S3, photoinitiated polymerization: a solution containing [VBIM][BF4], a crosslinker, and a photoinitiator was coated on the surface of the PET / UiO-66-NH2 film, cured under 365 nm UV light for 0.5-2 hours, and then dried to obtain a PIL-MOF composite film.

[0010] Preferably, in step S1, the concentration of nitric acid is 2-4 M, the PET film is immersed for 8-12 hours, and the drying temperature is 50-70°C.

[0011] Preferably, in step S2, the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 1:1; the volume ratio of acetic acid to DMF is 1:10-15; and the solvent thermal reaction temperature is 120°C.

[0012] Preferably, in step S3, the concentration of [VBIM][BF4] is 0.03-0.10 mol / L; the crosslinking agent is N,N'-methylenebisacrylamide, and the addition amount is 3-5% of the monomer mass; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the addition amount is 30-50% of the monomer mass.

[0013] The present invention also provides a PIL-MOF composite membrane obtained by the above preparation method, wherein the composite membrane comprises a UiO-66-NH2 metal organic framework layer grown on a PET substrate; a polyionic liquid polymer layer grafted on the surface; and the composite membrane has a thickness of 100-300 μm.

[0014] An application of the PIL-MOF composite membrane in gas separation, catalysis or antibacterial materials.

[0015] By adopting the above technical solution, the BET specific surface area of ​​the composite membrane prepared is 38-44 m 2 / g, retaining the UiO-66-NH2 microporous structure (0.5-0.9 nm); the CO2 adsorption capacity is increased by ≥30% compared with the unmodified membrane (303K, 1 bar); the CO2 / N2 selectivity remains above 85% of the initial value at 343K.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. Template-free hierarchical modification: Multi-step modification is achieved through in situ growth and photopolymerization, without the need for a template and simplifying the process.

[0018] 2. Size screening: The micropores (0.6-0.8 nm) of UiO-66-NH2 preferentially adsorb CO2 (3.3 Å) and repel N2 (3.6 Å).

[0019] 3. Charge guidance: The polycationic backbone of PIL undergoes Lewis interaction with the lone pair electrons of CO2, enhancing selectivity.

[0020] 4. Structural optimization: PIL seals the macropores of PET while retaining the internal pores of MOF, improving mechanical strength and permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a preparation flow chart of the present invention;

[0022] Figure 2 This is a diagram of the membrane separation mechanism of CO2 / N2 of the present invention;

[0023] Figure 3 This is an electron microscope image of PET / UiO-66-NH2 in Example 1 of the present invention;

[0024] Figure 4 This is an electron micrograph of PET / UiO-66-NH2@PIL in Example 1 of the present invention;

[0025] Figure 5 These are electron micrographs of the cross sections of PET, PET / UiO-66-NH2, and PET / UiO-66-NH2@PIL in Example 1 of the present invention;

[0026] Figure 6 Specific surface area test and pore size distribution diagram of PET / UiO-66-NH2 and PET / UiO-66-NH2@PIL in Example 1 of the present invention;

[0027] Figure 7 The carbon dioxide adsorption performance test and pore size distribution diagram of PET / UiO-66-NH2 and PET / UiO-66-NH2@PIL in Example 1 of the present invention are shown;

[0028] Figure 8 This is a test diagram of the CO2 / N2 mixed gas separation performance of the PET / UiO-66-NH2@PIL membrane in Example 1 of the present invention at different temperatures (pressure: 1 bar) and the long-term stability test of the PET / UiO-66-NH2@PIL membrane at 1 bar and 303 K. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings so that those skilled in the art can better understand the advantages and features of the present invention and thus more clearly define the scope of protection of the present invention. The embodiments described in the present invention are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making any creative work shall fall within the scope of protection of the present invention.

[0030] like Figure 1 As shown, the present invention provides a method for preparing a PIL-MOF composite membrane, comprising the following steps:

[0031] S1. The PET film was immersed in a 3M HNO3 solution for 12 hours and then washed with deionized water until neutral.

[0032] S2. Place the PET film in a mixed solution of zirconium tetrachloride, 2-aminoterephthalic acid, acetic acid, and DMF. The reaction is carried out in an oven at 120°C for 24 hours. After the reactor cools to room temperature, rinse the PET film several times with water and ethanol and dry it under vacuum at 60°C for 24 hours. The prepared film is designated PET / UiO-66-NH2.

[0033] S3. Disperse [VBIM][BF4] in water to prepare an aqueous solution, and add a crosslinking agent and a photoinitiator in sequence under stirring.

[0034] S4. The solution was evenly coated on the surface of the PET / UiO-66-NH2 film and polymerized under ultraviolet light for 15 minutes to obtain a PIL-MOF composite film.

[0035] S5. Before testing using a Micromeritics ASAP 2020 Plus HD88 analyzer, all samples were thermally activated at 120°C under vacuum for 24 hours. Subsequently, N2 adsorption-desorption measurements were performed at 77 K. Pore size distribution was calculated using the Barrett-Joyner-Halenda (BJH) model based on adsorption branch data, and specific surface area was calculated using the BET equation.

[0036]

[0037] Wherein, V: actual adsorption capacity (volume under standard conditions); Vm: monolayer saturated adsorption capacity; C: constant related to adsorption heat;

[0038] P: gas pressure; P0: saturated vapor pressure of adsorbed gas (P0 of N2 at 77k≈760mmHg).

[0039] S6. CO2 adsorption isotherm measurement was performed using a BEL Sorp-Max analyzer.

[0040] Prior to adsorption measurements, all samples underwent thermal pretreatment, including vacuum degassing at 120°C for 6 hours, to remove physically adsorbed contaminants. The activated samples were maintained under vacuum before CO2 gas was introduced into the system. Precise control of relative pressure (P / P0) was achieved through a programmed sequence that systematically adjusted the CO2 partial pressure to target values ​​(0.05, 0.2, 0.3, 0.5, 0.6, 0.8, 0.9, and 0.95). Gravimetric adsorption data, including time-dependent mass change, were continuously monitored using a high-resolution microbalance instrument until equilibrium conditions were reached (defined as mass stability within ±0.01% over 30 minutes).

[0041] S7. CO2 / N2 separation performance test of PET / UiO-66-NH2@PIL membrane using Wicke-Kallenbach permeation apparatus.

[0042] First, both permeation cells were securely sealed with O-rings, and the operating temperature was precisely controlled at 303 K. A CO₂ / N₂ mixture with a volume ratio of 15:85 (v / v) was introduced to the feed side of the membrane at a constant pressure of 1 bar. Argon was simultaneously introduced as a purge gas on the permeate side at a flow rate of 5 mL / min. After the system reached steady state, the composition of the permeate-side gas mixture was analyzed using a precalibrated gas chromatograph (GC, FULI 9790). The concentrations of each gas component were continuously monitored until the readings stabilized to ensure the accuracy and reliability of the test results. The gas permeability was finally calculated according to the following equation.

[0043]

[0044] Among them, P i is the permeability of component i (mol m −2 s −1 Pa −1 ), N i is the permeation rate of component i (mol s −l ), A is the effective membrane area (m 2), ΔPi is the transmembrane pressure difference of component i (Pa); GPU represents the unit of gas permeability. (1 GPU=3.35×10 −10 mol m −2 s –1 Pa −1 The dynamic permeation performance of the samples was tested using a Wicke-Kallenbach permeation apparatus at STP, and the gas permeability was calculated according to Eq.

[0045] The separation factor (SF, αij) of the mixed gas is calculated by the following equation:

[0046]

[0047] y ᵢ and y ⱼ are the molar ratios of components i and j on the permeate side, x ᵢ and x ⱼ are the molar ratios of components i and j on the feed side, respectively.

[0048] Example 1

[0049] S1. Soak a polyethylene terephthalate (PET) film (25.2 mg) in a mixture of water and nitric acid (HNO3) in a volume ratio of 1:2 for 5–7 h. Ultrasonic clean the film with deionized water until neutral, and then vacuum dry it at 60°C.

[0050] S2. Weigh zirconium tetrachloride (28.8 mg), add acetic acid (1.25 ml), and add DMF (15 ml). Ultrasonicate until the solid dissolves. Finally, weigh 2-aminoterephthalic acid (21.2 mg) and ultrasonicate until dissolved. Add a PET film to the mixed solution and soak for 2 hours. Transfer the mixture to a reactor and react at 120°C for 24 hours. After completion of the reaction, cool to room temperature, wash the product with ethanol, and dry it in a vacuum at 60°C to obtain the PET / UiO-66-NH2 film (26.46 mg).

[0051] S3. Disperse 1-vinyl-3-butylimidazolium tetrafluoroborate (IL) monomer in water to prepare 5 mL of a 0.03 mol / L solution. Add a crosslinker (2 mg of N,N-dimethylbisacrylamide) and a photoinitiator (30 mg of 1-hydroxycyclohexylphenyl ketone) sequentially while stirring. Evenly coat 2 mL of this solution onto the PET / UiO-66-NH2 film. Finally, transfer the PET / UiO-66-NH2 film to a 365 nm UV lamp and polymerize for 15 minutes. This yields a PET / UiO-66-NH2@PIL film (27.5 mg).

[0052] Comparative Example 1

[0053] S1. Soak a polyethylene terephthalate (PET) film (25.2 mg) in a mixture of water and nitric acid (HNO3) in a volume ratio of 1:2 for 5–7 h. Ultrasonic clean the film with deionized water until neutral, and then vacuum dry it at 60°C.

[0054] S2. Weigh zirconium tetrachloride (36 mg), add acetic acid (1.25 ml) to DMF (15 ml), and sonicate until the solid dissolves. Finally, weigh 2-aminoterephthalic acid (26.5 mg), sonicate until dissolved. Add a PET film to the mixed solution and soak for 2 hours. Transfer the mixture to a reactor and react at 120°C for 24 hours. After completion of the reaction, cool to room temperature, wash the product with ethanol, and dry it in a vacuum at 60°C to obtain the PET / UiO-66-NH2 film (27.72 mg).

[0055] S3. Disperse 1-vinyl-3-butylimidazolium tetrafluoroborate (IL) monomer in water to prepare 5 mL of a 0.03 mol / L solution. Add a crosslinker (2 mg of N,N-dimethylbisacrylamide) and a photoinitiator (30 mg of 1-hydroxycyclohexylphenyl ketone) sequentially while stirring. Evenly coat 2 mL of this solution on the PET / UiO-66-NH2 film. Finally, transfer the PET / UiO-66-NH2 film to a 365 nm UV lamp and polymerize for 15 minutes. This yields a PET / UiO-66-NH2@PIL film (28.76 mg).

[0056] Comparative Example 2

[0057] S1. Soak a polyethylene terephthalate (PET) film (25.2 mg) in a mixture of water and nitric acid (HNO3) in a volume ratio of 1:2 for 5–7 h. Ultrasonic clean the film with deionized water until neutral, and then vacuum dry it at 60°C.

[0058] S2. Weigh zirconium tetrachloride (28.8 mg), add acetic acid (1.25 ml), and add DMF (15 ml). Ultrasonicate until the solid dissolves. Finally, weigh 2-aminoterephthalic acid (21.2 mg), and ultrasonicate until dissolved. Add a PET film to the mixed solution and soak for 2 hours. Transfer the mixture to a reactor and react at 120°C for 24 hours. After completion of the reaction, cool to room temperature, wash the product with ethanol, and vacuum dry at 60°C to obtain the PET / UiO-66-NH2 film (26.46 mg).

[0059] S3. Disperse 1-vinyl-3-butylimidazolium tetrafluoroborate (IL) monomer in water to prepare 5 mL of a 0.05 mol / L solution. Add a crosslinker (2 mg of N,N-dimethylbisacrylamide) and a photoinitiator (30 mg of 1-hydroxycyclohexylphenyl ketone) sequentially while stirring. Evenly coat 2 mL of this solution onto the PET / UiO-66-NH2 film. Finally, transfer the PET / UiO-66-NH2 film to a 365 nm UV lamp and polymerize for 15 minutes. This yields a PET / UiO-66-NH2@PIL film (28.5 mg).

[0060] Comparative Example 3

[0061] S1. Soak a polyethylene terephthalate (PET) film (25.2 mg) in a mixture of water and nitric acid (HNO3) in a volume ratio of 1:2 for 5–7 h. Ultrasonic clean the film with deionized water until neutral, and then vacuum dry it at 60°C.

[0062] S2. Weigh zirconium tetrachloride (28.8 mg), add acetic acid (1.25 ml), and add DMF (15 ml). Ultrasonicate until the solid dissolves. Finally, weigh 2-aminoterephthalic acid (21.2 mg) and ultrasonicate until dissolved. Add a PET film to the mixed solution and soak for 2 hours. Transfer the mixture to a reactor and react at 120°C for 24 hours. After completion of the reaction, cool to room temperature, wash the product with ethanol, and dry it in a vacuum at 60°C to obtain the PET / UiO-66-NH2 film (26.46 mg).

[0063] S3. Disperse 1-vinyl-3-butylimidazolium tetrafluoroborate (IL) monomer in water to prepare 5 mL of a 0.03 mol / L solution. Add a crosslinker (2 mg of N,N-dimethylbisacrylamide) and a photoinitiator (30 mg of 1-hydroxycyclohexylphenyl ketone) sequentially while stirring. Evenly coat 2 mL of this solution onto the PET / UiO-66-NH2 film. Finally, transfer the PET / UiO-66-NH2 film to a 360 nm UV lamp and polymerize for 20 minutes. This yields a PET / UiO-66-NH2@PIL film (27.5 mg).

[0064] In summary, the present invention achieves in-situ growth of a UiO-66-NH2 layer on an acid-treated PET substrate, followed by grafting of a polyionic liquid layer onto the surface via UV-induced polymerization. This composite membrane combines the porous properties of a metal-organic framework with the functional properties of an ionic liquid, and has potential applications in gas separation, catalysis, and other fields. It also features a simple preparation process, high interfacial bonding strength, and stable product performance.

[0065] The descriptions and practices disclosed in this invention are easy to understand and comprehend for those skilled in the art, and modifications and refinements may be made without departing from the principles of the invention. Therefore, modifications and improvements made without departing from the spirit of the invention should also be considered within the scope of protection of this invention.

Claims

1. A method for preparing a PIL-MOF composite membrane, characterized in that: The steps include: Step S1, PET base film pretreatment: soak the PET film in 3M HNO3 solution for 8-12 hours, wash with deionized water until neutral and then dry; Step S2, in situ growth of UiO-66-NH2: zirconium tetrachloride is dissolved in acetic acid, kept at 80°C for 0.5-1.5 hours, and then cooled. DMF and 2-aminoterephthalic acid are added to form a precursor solution. The pretreated PET film is immersed in the solution for 1-3 hours, and then a solvothermal reaction is carried out at 110-130°C for 18-24 hours to obtain a PET / UiO-66-NH2 film. Step S3, photoinitiated polymerization: a solution containing [VBIM][BF4], a crosslinker, and a photoinitiator was coated on the surface of the PET / UiO-66-NH2 film, cured under 365 nm UV light for 0.5-2 hours, and then dried to obtain a PIL-MOF composite film.

2. The method for preparing a PIL-MOF composite membrane according to claim 1, wherein: In step S1, the nitric acid concentration is 2-4 M, the PET film soaking time is 8-12 hours, and the drying temperature is 50-70°C.

3. The method for preparing a PIL-MOF composite membrane according to claim 1, wherein: In step S2, the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 1:1; the volume ratio of acetic acid to DMF is 1:10-15; and the solvent thermal reaction temperature is 120°C.

4. The method for preparing a PIL-MOF composite membrane according to claim 1, wherein: In step S3, the concentration of [VBIM][BF4] is 0.03-0.10 mol / L; the crosslinker is N,N'-methylenebisacrylamide, and the addition amount is 3-5% of the monomer mass; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the addition amount is 30-50% of the monomer mass.

5. The PIL-MOF composite membrane obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The composite film comprises a UiO-66-NH2 metal organic framework layer grown on a PET substrate and a surface grafted polyionic liquid polymer layer; and the thickness of the composite film is 100-300 μm.

6. Use of the PIL-MOF composite membrane according to claim 5 in gas separation, catalysis or antibacterial materials.

Citation Information

Cited By

  • Super-hydrophobic PVDF-UiO-66-PFOC composite membrane as well as preparation method and application thereof

    CN121846922A